Ответы и объяснения

Лучший Ответ!
2013-05-17T01:16:39+04:00

((x+y)*5)+((x-y)*3)=230

((x+y)*2)+((x-y)*7)=237

 

((x+y)*5)+((x-y)*3)=230

5x+5y+3x-3y-230=0

8x+2y-230=0

y=-4x+115

 

((x+y)*2)+((x-y)*7)=237

9x-5y-237=0

9x-5*(-4x+115)-237=0

9x+20x-575-237=0

29x-812=0

x=812/29

x=28

 

8x+2y-230=0

8*28+2y-230=0

224+2y-230=0

-6+2y=0

y=6/2

y=3

2013-05-17T01:24:26+04:00

 ((x+y)*5)+((x-y)*3)=230

 ((X+y)*2)+((x-y)*7)=237

 

(5x+5y)+(3x-3y)=230

(2x+5y)+(3x-3y)=237

 

8x+2y=230

9x-5y=237

 

4x+y=115

9x-5y=237

 

y=115-4x

9x-5*(115-4x)=237

 

9x-5*(115-4x)=237

 

9x-575+20x=237

29x=812

x=28

 

 

y=4*28+y=115

y=112+y=115

y=115-112

y=3

Както так))